Intervarietal and intravarietal genetic structure in Douglas‐fir: nuclear SSRs bring novel insights into past population demographic processes, phylogeography, and intervarietal hybridization. Issue 9 (3rd April 2015) - van Loo, Marcela; Hintsteiner, Wolfgang; Pötzelsberger, Elisabeth; Schüler, Silvio; Hasenauer, Hubert
Abstract: Douglas‐fir ( Pseudotsuga menziesii ) is one of numerous wide‐range forest tree species represented by subspecies/varieties, which hybridize in contact zones. This study examined the genetic structure of this North American conifer and its two hybridizing varieties, coastal and Rocky Mountain, at intervarietal and intravarietal level. The genetic structure was subsequently associated with the Pleistocene refugial history, postglacial migration and intervarietal hybridization/introgression. Thirty‐eight populations from the USA and Canada were genotyped for 13 nuclear SSRs and analyzed with simulations and traditional population genetic structuring methods. Eight genetic clusters were identified. The coastal clusters embodied five refugial populations originating from five distinct refugia. Four coastal refugial populations, three from California and one from western Canada, diverged during the Pleistocene (56.9–40.1 ka). The three Rocky Mountain clusters reflected distinct refugial populations of three glacial refugia. For Canada, ice covered during the Last Glacial Maximum, we present the following three findings. (1) One refugial population of each variety was revealed in the north of the distribution range. Additional research including paleodata is required to support and determine whether both northern populations originated from cryptic refugia situated south or north of the ice‐covered area. (2) An interplay between intravarietal gene flow of different refugial populations and intervarietal gene flow by hybridization and introgression was identified. (3) The Canadian hybrid zone displayed predominantly introgressants of the Rocky Mountain into the coastal variety. This study provides new insights into the complex Quaternary dynamics of this conifer essential for understanding its evolution (outside and inside the native range), adaptation to future climates and for forest management. Abstract : This study examined the genetic structure of the North American conifer Douglas‐fir ( Pseudotsuga menziesii ) and its two hybridising varieties, coastal and Rocky Mountain, at intervarietal and intravarietal level using 13 nuclear SSRs. The genetic structure was subsequently associated with the Pleistocene refugial history, postglacial migration and inter‐varietal hybridisation/introgression.